Microencapsulação do extrato de mirtilo (Vaccinium ashei): avaliação da estabilidade e efeito antiproliferativo em células de adenocarcinoma de cólon - Rosa, Jéssica Righi da (2021)
The microencapsulation of anthocyanic compounds has become an efficient alternative in protecting and increasing the bioavailability of weakly stable compounds. Studies have been carried out in order to verify the anticarcinogenic effect of blueberry, but a wide range has taken into account only purified extracts, not taking into account the instability of anthocyanin compounds in the gastrointestinal system. Based on that, the objective of the present work was to microencapsulate the blueberry extract (Vaccinium ashei) by the spray drying method using maltodextrin-DE20, hi-maize, gum arabic and inulin as wall material, to evaluate its stability under different conditions of storage (60 days), its bioavability under simulated gastrointestinal conditions and its antiproliferative effect on colon adenocarcinoma cells (HT-29). Microencapsulation was carried out in laboratory scale spray drying using 140 °C of inlet air, four feeding solutions were prepared: standard formulation (S): maltodextrin DE20, hi-maize; T1: DE20 maltodextrin, hy-maize, inulin; T2: maltodextrin DE20, hi-maize, gum arabic; and T3: maltodextrin DE20, hi-maize, inulin and gum arabic. The microcapsules were evaluated for moisture content, solubility, encapsulation efficiency, particle size, morphology, total phenolic compounds, antioxidant capacity, stability of total monomeric anthocyanins under different storage conditions and the simulated gastrointestinal system. Subsequently, the microcapsule that presented the best results against the analyzes performed was selected and evaluated when its cell viability (MTT), nitric oxide (NO) and anti-proliferative effect (chlorogenic analysis, cell cycle and western blot) against colon cancer cells (HT-29) was performed. The microcapsules obtained in the present study showed high encapsulation efficiency from 96.80 to 98.83%. Among the parameters analyzed, the T3 formulation showed the lowest values of constant degradation (k) at the storage temperatures tested, with an emphasis on the freezing temperature, corresponding to the lowest loss during storage and, consequently, a longer half-life (t ½ ) being 913.41 days. This same treatment was shown to be effective in the preservation and improved delivery of anthocyanin compounds when compared to the free extract. The blueberry extract microcapsule showed a slight decrease in viability (24 hours) and anti-proliferative capacity (48 and 72 hours) against HT-29. The microcapsules were effective in increasing oxidative stress in HT-29 cells at concentrations between 3000 and 9000 μg/mL. Concentrations of 7000, 8000 and 9000 μg/mL showed a decrease in colony formation. However, the results found in the present study also suggest that the pathways of action of microcapsules against cancerous lines still need to be better elucidated, allowing a greater understanding of the metabolism of microcapsules.